A comprehensive assessment of thermophysical properties of MXene doped Polyethylene glycol 400 for cold chain logistics - Paul Nadakkal, John; Samykano, Mahendran; Kumar Pandey, Adarsh Kumar; Kadirgama, Kumaran; Jacob, Jeeja; Saidur, Rahman Md (Elsevier B.V., 2025)
Organic Phase change materials (PCMs) are commonly utilized in cold-chain logistics applications. Numerous logistics firms have successfully demonstrated the commercial viability of PCM-integrated shipping containers. Enhancing the thermal characteristics of PCMs could contribute to increased viability and sustainability. This research evaluates the thermophysical viability of a novel phase change composite, which could be used for a cold chain logistics system. Specifically, this research aims to shed light on energy storage systems that employ nanocomposites operating in lower (5–10 °C) temperature ranges. Polyethylene Glycol is a commonly used organic PCM as the molecular weight can be tuned according to necessities. MXene is a 2-dimensional nanomaterial with excellent properties. Initially, MXene nanoflakes were produced using a wet chemical process. The purity of the synthesized MXene flakes was verified by XRD analysis. The (PEG400/MXene) nanocomposite was synthesized using a facile two-step synthesis. From the viewpoint of MXene flake addition, the thermophysical properties of the nanocomposite PCM were analyzed in this article. A series of nanocomposites were methodically formulated by doping MXene flakes in varying concentrations (0-1 wt%) in PEG 400 to optimize their thermal properties. A boost of 17.98 % in thermal conductivity was noted for a maximum (1 wt%) loading of MXene nanoparticles. The phase change enthalpy of the nanocomposite was 100.68 kJ/kg. The thermo gravimetric analysis showed that all nanocomposites had decomposed above 350 °C, well above the permitted working temperature range. The solar transmittance value is as low as 0.127 %, showing that the NEPCCs can absorb the entire inherent solar spectrum. The comprehensive thermophysical characterization results indicate that the developed nanocomposite holds tremendous potential for integration in cold chain logistics systems.